Brief Psychological Screening Questions can be Useful for Ruling Out Psychological Conditions in Patients with Chronic Pain - Vaegter, H.; Handberg, G.; Kent, Peter (2017)
Objectives: Psychological symptoms are highly prevalent in chronic pain patients. Timely and accurate identification may enable individualized treatment and improve outcomes. The aims of this study were to (1) investigate the concurrent validity of brief psychological screening questions assessing anxiety, fear of movement, stress, pain catastrophization, and depression in chronic pain patients, and (2) to determine screening question cut-points at which the likely probability of having these psychological states was <10%. Materials and Methods: Responses to 1-item or 2-item screening questions within each of these 5 psychological constructs were compared with those of validated full-length questionnaires in 894 patients with diverse chronic pain conditions. Results: Compared with scores from full-length questionnaires, brief screening question scores had correlations between 0.54 and 0.66, and area under the curve between 0.79 and 0.83. At the dichotomized threshold scores that we chose, the posttest probability after a negative test result ranged from 6.5% to 8.6% for all these psychological constructs, except fear of movement. The pretest probability was so high (70%) for fear of movement that no threshold resulted in a posttest probability (negative test result) that was below 10%. Discussion: Use of these screening tests and scoring thresholds would have correctly identified that between 38.5% and 60.5% of the sample were unlikely to have these psychological states (true negatives), with a false-negative rate between 3.4% and 5.3%. This would allow clinicians to focus on whether there are other patient attributes in those patients requiring more thorough investigation using comprehensive validated questionnaires or structured clinical interviews.